Broken Theory - Sondheim, Alan (punctum books, 2022)
Broken Theory is a jettisoned collection of fragmentary writing, collected and collaged by new media artist, writer, musician, and theorist Alan Sondheim. Folding theoretical musings, text experiments, and personal confessions into a single textual flow, it examines the somatic foundations of philosophical theory and theorizing, discussing their relationships to the writer and body, and to the phenomenology of failure and fragility of philosophy's production. Writing remains writing, undercuts and corrects itself, is always superseded, always produced within an untoward and bespoke silo - not as an inconceivable last word, but instead a broken contribution to philosophical thinking. The book is based on fragmentation and collapse, displacing annihilation and wandering towards a form of "roiling" within which the text teeters on the verge of disintegration. In other words, the writing develops momentary scaffoldings - writing shored up by the very mechanisms that threaten its disappearance. Broken Theory is prefaced by a text from Maria Damon and followed by an extensive interview with art historian Ryan Whyte.